Significance of F-18 FDG PET/MRI in the search for the etiology of inflammation of unclear origin and fever of unknown origin - Rohan, Tomáš; Hložanka, Petr; Dostál, Marek; Macek, Tomáš; Fojtík, Zdeněk; Šprláková-Puková, Andrea; Keřkovský, Miloš (European journal of radiology, 2024)
PURPOSE: To evaluate the contribution of F-18 FDG-PET/MRI in the search for the etiology of the inflammation of unknown origin (IUO) and fever of unknown origin (FUO). MATERIAL AND METHODS: The study included 104 patients who underwent F-18 FDG-PET/MRI for IUO or FUO. The sensitivity, specificity, predictive values of the PET/MRI findings in relation to the final diagnosis of IUO/FUO were evaluated. A five-point Likert scale was used to semiquantitatively assess the probability of the cause of IUO/FUO based on PET/MRI finding. Furthermore, clinical (fever, arthralgia, weight loss, night sweats, age) and laboratory (C-reactive protein, leukocytes) parameters were monitored and compared with the true positivity rate of PET/MRI. RESULTS: In patients with definitively identified etiology of FUO and IUO, FDG-PET/MRI achieved a sensitivity of 96 %, specificity of 82 %, and positive and negative predictive values of 92 and 90 %. The cause of the IUO was determined in 71 patients (68.3 %). In 33 (31.7 %) patients, the etiology of IUO/FUO remained unknown, while in 25 (75.8 %) of them the symptoms resolved spontaneously and in 8 (24.2 %) patients they persisted without explanation even after 12 months of the follow-up. The most significant parameter in relation to subsequent PET/MRI finding was increased level of CRP, which was present in 96 % of true positive PET/MRI and normal CRP level was present in 56 % of true negative PET/MRI. CONCLUSION: Based on this study, FDG-PET/MRI is a suitable alternative for the investigation of IUO/FUO, this imaging technique has a very high sensitivity and negative predictive value.
Keywords: Radiopharmaceuticals; Inflammation; radiofarmaka; fluorodeoxyglukosa F18; pozitronová emisní tomografie; C-reaktivní protein; lidé; zánět; Fluorodeoxyglucose F18; Fever of Unknown Origin; C-Reactive Protein; horečka neznámého původu; Positron-Emission Tomography; Humans